#TITLE_ALTERNATIVE# - HIDAYATULLAH (NIM 15104013), ASYSYARIF
The objective of this study is to determine depth of penetration (DOP) of light through water column and attenuation rate (k) of optical intensity using SPOT (Satellite Pour I'Observation de la Terre) image at Semak Daun Island, Kepulauan Seribu, North Jakarta. Methodology that is applied in this study is started with image classification into 10 classes of seabed coverage that have a homogeneous type of seabed coverage, then it is continued with determination of DOP and k for every formed class. This methodology has reduced error from different type of seabed coverage. Determination of DOP and k values are done with two methods which are graphical method (visual interpretation) and Jupp's method. The result shows that only band 1 can be used to represent DOP and k values because the result of k values do not match with the theory. Graphical method gives DOP of 5.5 m and k of 0.0670 m-1 for class number 1, DOP of 5.5 m and k of 0.0575 m-1 for class number 2, DOP of 4.5 m and k of 0.0339 m-1 for class number 3, and DOP of 5.5 m and k of 0.0453 m-1 for class number 4. Jupp's method gives DOP of 14.2 m and k of 0.0703 m-1 for class number 1, DOP of 18.4 m and k of 0.0544 m-1 for class number 2, DOP of 16.4 m and k of 0.0611 m-1 for class number 3, and DOP of 14.3 m and k of 0.0698 m-1 for class number 4. Estimated DOP for every class of seabed coverage vary at an accuracy of ranging from R2=7.7% to R2=68.1%.